Presentations of idiopathic hemorrhagic diarrhea syndrome in dogs in relation to meteorological factors - Michelle Karnstedt; Amna Asif; Terence Z Sibanda; Romy M Heilmann (Journal of Veterinary Internal Medicine, 2026)
Abstract Background Causes for idiopathic acute hemorrhagic diarrhea syndrome (AHDS) in dogs remain uncertain. Recent discoveries suggest a role for enterotoxin-producing Clostridium perfringens, but the triggers for toxin production and AHDS onset are unknown. Meteorological factors have not been examined as a possible AHDS trigger. Hypothesis/Objectives Retrospective case–control study aiming to examine the effects of weather conditions and weather changes on the prevalence of idiopathic AHDS. Animals Dogs (n = 412) presented with acute gastrointestinal (GI) clinical signs between January 2016 and January 2021 at a tertiary veterinary care center. Methods Dogs were stratified into 3 groups: idiopathic AHDS, acute gastroenteritis, and other causes for acute GI signs. This categorization was based on the combination of patient history, physical examination, and further diagnostic evaluation (eg, laboratory and imaging diagnostics). Meteorological data were extracted for each dog based on the geocodes of their primary location and were analyzed for associations with AHDS presentations by building a random forest model and calculating odds ratios. Results Increased wind speeds and shortwave radiation exposure, lower temperatures and sunlight intensity, and dry weather were linked to increased idiopathic AHDS presentations in dogs in the investigated geographical region. Conclusions and clinical importance Our explorative study provides an outlook for prospective investigations to further evaluate potential effects of meteorological factors on the gut-brain-microbiome axis and their role in the development of idiopathic AHDS. In addition to shedding more light on pathogenetic mechanisms of an idiopathic condition, understanding these environmental and weather-related effects could be important in predicting and managing this condition.